Patient’s perception of recovery after osteotome-mediated sinus floor elevation with Bio-Oss collagen compared with no grafting material: a randomized single-blinded controlled trial - Thomas Starch-Jensen (International Journal of Implant Dentistry, 2021)
Abstract Background Osteotome-mediated sinus floor elevation with or without a grafting material is associated with high implant survival, intrasinus bone gain, and low frequency of complications. However, patient’s perception of recovery and satisfaction with the surgical intervention are rarely reported. The objective of the present randomized controlled trial was to assess patient’s perception of recovery after osteotome-mediated sinus floor elevation with Bio-Oss collagen compared with no grafting material. Forty healthy patients were randomly allocated to Bio-Oss collagen or no grafting material. Oral health-related quality of life was assessed by Oral Health Impact Profile-14 at enrollment. Patient’s perception of recovery was assessed by self-administrated questionnaires and visual analog scale evaluating pain, social and working isolation, physical appearance, duration and quality of life alterations, eating and speaking ability, diet variations, and sleep impairment after 1 week and 1 month, respectively. Descriptive statistics was expressed as mean percentage with standard deviation. Correlation between impaired oral health-related quality of life, age, gender, and recovery were assessed by T test. Level of significance was 0.05. Results Osteotome-mediated sinus floor elevation is associated with high patient satisfaction, limited postoperative discomfort, and willingness to undergo similar surgery. Influence on patient’s daily life activities seems to be minimal and limited to the first postoperative days. Most patients managed to return to work and their routine daily activities after 0-2 days. Impaired preoperative oral health-related quality of life, gender, or younger age seems not to predispose for delayed recovery. However, number of days with pain, eating difficulties, and sleep disturbances were significantly increased with Bio-Oss collagen compared with no grafting material (P<0.05). Conclusion Patient’s discomfort seems to be minimal and limited to the first postoperative days following osteotome-mediated sinus floor elevation with or without a grafting material. Impaired preoperative oral health-related quality of life, gender, or younger age seems not to predispose for delayed recovery.